GEOTHERMAL SYSTEM MODELING BASED ON THE GRAVITY DATA OF WAY SELABUNGâS GEOTHERMAL FIELD, SOUTH SUMATERA - Farhanto, Doni
Indonesia is one of the countries with the highest potential for geothermal resources, making it the fourth largest in the world. One of the geothermal areas in Indonesia is the Way Selabung Geothermal Field, South Sumatra. The purpose of this study is to create a conceptual model of the geothermal system from the Way Selabung Geothermal Field. In this study, the data used are Complete Bouguer Anomaly (CBA) data and topographic data obtained from the PSDMBP research results in 2011 in the Way Selabung Geothermal Field. Then the data was processed using two different methods, namely the moving average method and the second order polynomial to obtain regional and residua anomaly maps. The results of the maps anomaly value of the two methods were compared and the one that was most optimal was chosen for further data processing. The residual anomaly shows anomaly results with a range of values from -13 to 9 mGal and -18 to 20 mGal, respectively. From the residual maps produced by the two methods, the second order polynomial method residual anomaly map was chosen because it shows the geological conditions of the Akarjangkang lava and Ranau pyroclastic, which are the focus of the research which is more suitable for the geological conditions of the Way Selabung Geothermal Field. Based on the modeling results, the bedrock in this area is interpreted as a unit of sandstone (?? = -0.19 gr / cc) which is tertiary in age. In addition, the modeling results show the intrusion of basalt andesite I & II (?? = +0.36 & +0.37 gr / cc) and Akarjangkang lava (?? = +0.39 gr / cc). In the geothermal conceptual model of the Way Selabung Geothermal Field, there is an intrusion of andesite-basalt I as a Heat Source. Then, the layer that becomes the reservoir rock is the sandstone layer and the caprock layer is the old breccia layer